Urban Eco-Communities in Australia Real Utopian Responses to the Ecological Crisis or Niche Markets? - Cooper, Liam.; Baer, Hans A.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book offers one of the first detailed anthropological studies of emergent ecotopianism in urban contexts. Engaging directly with debates on urbanisation, sustainability and utopia, it presents two detailed ethnographic case studies of inner urban Australian eco-communities in Adelaide and Melbourne. These novel responses to the ecological crisis - real social laboratories that attempt to manifest a vision of the 'eco-city' in microcosm - offer substantial new insights into the concept and creation of sustainable urban communities, their attempts to cultivate ways of living that are socially and ecologically nourishing, and their often fraught relationship to the capitalist city beyond. These studies also suggest the opportunities and limitations of moving beyond demonstration projects towards wider urban transformation, as well as exposing the problems of accessibility and affordability that thwart further urban eco-interventions and the ways that existing projects can exacerbate issues of gentrification and privilege in a socially polarised city. Amidst the challenges of the capitalist city, climate change and ecological crisis, this book offers vital lessons on the potential of urban sustainability in future cities.
1 Introduction -- 2 Building the Future: Real Ecotopian Models in the Age of Climate Change -- 3 Christie Walk: An Urban Eco-Village in an Increasing Hot City -- 4 WestWyck: An Urban Eco-Village in the World's Putatively Most Liveable City -- 5 Enacting Real Ecotopia in the City: Ontological and Ecological Characteristics and Contradictions -- 6 Prefiguring Ecopolis: Ecotopian Cities or Niche Markets? -- 7 Conclusion.
Keywords: Sociology, Urban; Human geography; Urban ecology (Biology).; Sustainability; Urban Sociology; Human Geography; Urban Ecology; Sustainability